2015
DOI: 10.1097/fbp.0000000000000155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute and chronic social defeat stress are differentially mediated by the dynorphin/kappa-opioid receptor system

Abstract: Accumulating evidence indicates that kappa-opioid receptors (KORs) and their endogenous ligand dynorphin (DYN) can play important roles in regulating the effects of stress. Here, we examined the role of KOR systems in the molecular and behavioral effects of acute (1-day) and chronic (10-day) social defeat stress (SDS) in mice. We found that acute SDS increased DYN mRNA levels within the nucleus accumbens (NAc), a key element of brain dopamine (DA) systems. In contrast, chronic SDS produced long-lasting decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 50 publications
6
52
0
Order By: Relevance
“…In California mice, real-time PCR analysis of prodynorphin mRNA in the NAc showed no effects of social defeat, although mean levels were lower in stressed males and females [46]. In male C57Bl6 mice, a single episode of defeat increased prodynorphin mRNA in the NAc but 10 days of defeat reduced prodynorphin mRNA [17]. Interestingly, social defeat also decreased in prodynorphin mRNA in the medial preoptic area of sexually experienced male California mice (Kowalcyzk and Trainor, in prep.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In California mice, real-time PCR analysis of prodynorphin mRNA in the NAc showed no effects of social defeat, although mean levels were lower in stressed males and females [46]. In male C57Bl6 mice, a single episode of defeat increased prodynorphin mRNA in the NAc but 10 days of defeat reduced prodynorphin mRNA [17]. Interestingly, social defeat also decreased in prodynorphin mRNA in the medial preoptic area of sexually experienced male California mice (Kowalcyzk and Trainor, in prep.).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, aggressive contests occurred over a 10-day period, a much longer time frame than studies examining effects of KOR antagonists in the context of stress. Similarly, administration of the long lasting KOR antagonist JDTic before 10 days of social defeat stress did not prevent the development of decreased social interaction or anhedonia in male mice [17]. These data suggest that, over time, neuroadaptations induced by stress may alter the function of KORs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings on stress-induced dynorphin changes are inconsistent. A recent study showed a reduction in the dynorphin mRNA levels following chronic exposure to social defeat stress in adult mice (Donahue et al, 2015). Conversely, there is evidence for increased tissue concentrations of dynorphin and dynorphin mRNA levels following repeated exposure to ethanol, which is considered a stressor, in adult rats (Lindholm et al, 2000;Kissler et al, 2014).…”
Section: Si-induced Potentiation Of Kor System Responsivenessmentioning
confidence: 99%
“…KOPr signaling tone is upregulated in depressive states, following both stress (Donahue et al 2015; Land et al 2008; Lucas et al 2011; Reed et al 2012) and chronic cocaine exposure, largely through increased mRNA transcription and activity of its endogenous peptides, the dynorphins (Fagergren et al 2003; Sivam 1996; Spangler et al 1996; Unterwald et al 1994; Valenza et al 2016). Activation of KOPr induces dysphoria in humans, as well as place aversion and depressive-like behaviors in preclinical models (Bruchas et al 2009; Carlezon et al 2006; Chefer et al 2013; Land et al 2008; Mucha and Herz 1985; Pfeiffer et al 1986a; Todtenkopf et al 2004).…”
Section: Introductionmentioning
confidence: 99%